2000
DOI: 10.1097/00006254-200008000-00011
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of the Demand for and Cost of Preimplantation Genetic Diagnosis in the United Kingdom

Abstract: Research in the field of preimplantation genetic diagnosis (PGD) has concentrated on increasing the number of diseases diagnosed, different strategies for single cell analysis and improving efficiency and reliability. Of equal importance are clinical issues such as the demand for and cost of PGD. This study assesses patient awareness of PGD and its potential benefits; additionally the awareness, attitudes and referral patterns of Assisted Conception Units, Regional Genetics Centres and Health Authorities (fund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…An additional source of discrepancy about PGD for hereditary cancers versus other genetic disease is the concept of increased susceptibility versus inevitability. 20,50 FAP is an early-onset disease which may influence testing at a young age, 51 compared with BRCA testing which is typically not recommended before the age of 25 years. 52 A 2009 study showed that less than half of clinics surveyed that perform PGD and require genetic counseling assessed how well patients understood the information disclosed during a counseling session.…”
Section: Acceptability Of Pgd Among High-risk Consumersmentioning
confidence: 99%
“…An additional source of discrepancy about PGD for hereditary cancers versus other genetic disease is the concept of increased susceptibility versus inevitability. 20,50 FAP is an early-onset disease which may influence testing at a young age, 51 compared with BRCA testing which is typically not recommended before the age of 25 years. 52 A 2009 study showed that less than half of clinics surveyed that perform PGD and require genetic counseling assessed how well patients understood the information disclosed during a counseling session.…”
Section: Acceptability Of Pgd Among High-risk Consumersmentioning
confidence: 99%
“…Developing a PGD program requires a considerable initial investment in expensive equipment (2). For single-gene defects, like CF ( F508) or SMA (telomeric deletion), a single-cell genetic test can be developed for standard gel electrophoresis (Bio-rad electrophoresis unit: ∼500 US$) or fragment analysis (automated fluorescent DNA sequencer: ∼100,000 US$).…”
Section: Discussionmentioning
confidence: 99%
“…However, many diseases are caused by a spectrum of mutations (e.g., cystic fibrosis (CF) and beta-thalassemia), with some occurring very rarely within the general population. Since developing a new assay involves a considerable investment of time and resources (2), it is impractical for PGD centers to standardize protocols case by case. Therefore, advancements in the diagnosis of singlegene defects have all stemmed from the necessity to make each test rapid, accurate, and cost-effective, while also offering it to as large a patient base as possible.…”
Section: Introductionmentioning
confidence: 99%